Comparison of Hepatic Parameters Following Administration of Antihypertensive, Hypolipidemic and Hypoglycemic Drugs - Afshan Siddiq; Rafeeq Alam Khan; Afaq Ahmed Siddiqui (Journal of Basic & Applied Sciences, 2013)
The risk of additive effects of drugs has remained a continuous concern while prescribing more than one drug to a patient, and it becomes more of a problem when the patient suffers from various diseases simultaneously. In this reasearch the drug taking pattern of elderly patients was kept in mind and the antihyperlipidemic, oral hopoglycemic and antihypertensive commonly prescribed in combinations or as individual agents were given to the rabbits for period of two months and their effects on liver function tests were noted. As compared to control rabbits, Acarbose and Glibenclamide decreased Direct bilirubin (DBR), where as Lisinopril and Amlodipine increased it (P<0.05). Atorvastatin and Amlodipine increased Total bilirubin (TBR) (P<0.05). Acarbose and Metformin increased, where as Atorvastatin decreased Glutamic-Pyruvic Transaminase (GPT) (P<0.05). Metformin and Lisinopril decreased (P<0.05) where as Losartan increased ALP(alkaline phosphatase) (P<0.005). Losartan and Atorvastatin increased Gamma Glutamyl Transferase γ-GT (P<0.005).